Perancangan Sistem Informasi Abensi Berbasis Website Pada Rumah Sakit Prima Pekanbaru - Edo Arribe; Vania Marisa; Willy Fadhilah Wira Yudha (Utility Project Solution, 2023)
Attendance is one of the important indicators in evaluating employee performance in a company to determine the number of employee attendance. Attendance can be in the form of data extraction that contains the time of arrival and departure. Previously, Prima Pekanbaru Hospital had implemented a fingerprint attendance system, but the attendance recording system in the company is still less practical and accurate. The problems identified based on observations are data extraction related to absenteeism and non-fully digitized permissions. For absenteeism and permissions, employees still use manual paper-based methods and have to deliver them to the company, which is ineffective in terms of time and cost. In relation to this, a more comprehensive information system design is implemented where all attendance data extraction is integrated into one system. In addition to that, analysis and design of a web-based attendance information system are conducted using the Waterfall system development method and Unified Modeling Language (UML), with structured and systematic data storage using the MySQL database. The designed computerized attendance system is expected to provide convenience and satisfaction to the company and have a positive impact in reducing the percentage of errors, omissions, or data loss that may occur in attendance data recording, data search, and attendance recap calculations.